The effectiveness of educational programs on parenting stress and coping mechanism among parents of children with autism spectrum disorder: a systematic review - Al-Oran, Haytham Mohammad; Lee, Khuan; Tan, Kit Aun; Lim, Poh Ying (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
The aim of this systematic review was to evaluate the effectiveness of educational programs on parenting stress and coping mechanism among parents of children with Autism Spectrum Disorder. Our current review retrieved the articles from databases such as CINAHL, Springer, Ovid, PubMed, Google Scholar, and EBSCO host. Only articles published between the years of 2000 and 2018 in these databases were recruited using keywords such as Autism Spectrum Disorder, education program, parenting stress, coping mechanism, and coping strategies. The search generated 17 articles; 8 articles were relevant. This systematic review provides an important opportunity to advance our understanding of the effectiveness of the educational program for reducing parenting stress and improving coping mechanism among parents of children with Autism Spectrum Disorder. Nurses could also have a pivotal role in delivering the educational program for parents of children with ASD.